Review of Contemporary Techniques for Minimally Invasive Coronary Revascularization - Fatehi Hassanabad, Ali (Innovations (Phila), 2021)
Minimally invasive coronary revascularization techniques aim to avoid median sternotomy with its associated complications, while facilitating recovery and maintaining the benefits of surgical revascularization. The 3 most common procedures are minimally invasive coronary artery bypass grafting, totally endoscopic coronary artery bypass, and hybrid coronary revascularization. For a variety of reasons, including cost and technical difficulty, not many centers are routinely performing minimally invasive coronary revascularization. Nevertheless, many studies have assessed the safety and efficacy of each of these procedures in different clinical contexts. Thus far results have been promising, and with the evolution of procedural techniques, these approaches have the potential to redefine coronary revascularization in the future. This review highlights the current state of minimally invasive coronary revascularization techniques by exploring their benefits, identifying barriers to their adoption, and discussing future potential paradigms.